The Effect of Chemical and Biological Fertilizers on Yield, Yield Components and Protein Content of Sesame Grain (Sesamum indicum L.) under Different Irrigation Regimes - M Moradi Shahdadi; M Dejam; M Madandoust; M. R Baziar (پژوهشهای زراعی ایران)
IntroductionThe production of oil, especially organic oil, from oilseed plants is important, so that oilseed plants occupy the second food reserves in the world after cereals. Sesame is an industrial plant that can be cultivated in arid and semi-arid regions, however, its growth and yield are limited by drought stress. Drought stress is considered as one of the most important factors limiting the performance of plants. Therefore, proper and principled management of agricultural inputs, including fertilizers, can partially reduce the negative effect of drought stress. This study aimed to examine the effects of chemical fertilizers, biofertilizers, and humic acid—applied individually and in combination—on the yield, yield components, and protein content of sesame grain under different irrigation regimes.Materials and MethodsThis research was carried out in the form of a split plot experiment based on the complete blocks design with three replications during the 2022 and 2023 at a research farm in Hormozgan province. The experimental treatments included irrigation regimes at three levels (irrigation after 40, 60 and 80% moisture discharge as main plots and fertilizer treatments at seven levels (control (F1), 100% need plant to phosphorus chemical fertilizer (F2), plant inoculation with arbuscular mycorrhizal fungus (F3), humic acid (F4), 50% chemical fertilizer+mycorrhiza (F5), 50% chemical fertilizer+humic acid (F6) and 50% chemical fertilizer+Mycorrhiza+humic acid (F7) was in sub-plots. In this experiment, agronomic characteristics, yield, yield components and grain protein of sesame were investigated.Results and DiscussionThe results showed that irrigation regimes and fertilizer treatments showed a significant effect on the studied characteristics of sesame. Irrigation at 80% moisture reduced the plant height, the number of sub-branches, the number of leaves, the number of capsules, the weight of 1000 grain, the biological yield, the grain yield and the harvest index by nearly 35, 50, 37, 48, 42, 52, 61 and 13% respectively compared to irrigation at 40%. Therefore, increasing the plant's access to water improved cell growth and division by increasing cell mass. It has been reported that there is a direct relationship between the increase of drought stress and the decrease of each of the growth characteristics of the plant, so that drought stress can cause damage to the growth characteristics and plant yield components, depending on the growth stage, which will reduce economic yield. On the contrary, irrigation after 80% treatment led to an increase in nitrogen and grain protein concentration compared to irrigation after 40%. In addition, among the fertilizer treatments, the F7 treatment resulted in an increase in growth characteristics, yield components, yield and nitrogen content of sesame grain. In this research, the individual application of mycorrhiza and humic acid could have more favorable growth characteristics than the application of 100% phosphorus chemical fertilizer or its non-application. Different mechanisms have been described for the effect of mycorrhizae on the growth characteristics of plants, such as increasing the absorption of nutrients, nitrogen, phosphorus, and low-use elements. Because in a mycorrhizal plant compared to a non-mycorrhizal plant, the creation of a wide hyphal network of fungi between the soil and the root provides a large surface for the absorption of nutrients. Humic acid is also able to improve the vegetative characteristics of plants by increasing the photosynthetic capacity, leaf water content and the metabolism of antioxidant compounds. ConclusionIncreasing water availability, along with the combined application of reduced amounts of chemical fertilizers, mycorrhiza, and humic acid, resulted in improved quantitative and qualitative yield of sesame. The enhanced performance of the combined treatments compared to other fertilizer treatments can be attributed to the lack of organic matter in the region's soil. The best results were observed with the integrated treatment of mycorrhiza, humic acid, and chemical fertilizers, as it provided the plant with the most access to essential nutrients.